Design and Implementation of Online Students’ Complaint (Case Study of English Study Program at Victory University, Sorong) - Manuhutu, MA; Uktolseja, LJ (International Journal of Computer Sciences and Engineering, 2025)
An information system is a very famous tool in this digital era. People all over this world use this tool to get and share information. Computer based system is one type of information system that very often to use in this era. It touches over all the sides of life nowadays. It can avoid errors caused by user or staff at the organization itself besides of easy and fast access to deliver new information. Online students’ complaint is an information system used to help study program in accepting criticism and suggestions by the students to help it improve the services. This research will reduce paper usage, time and energy. This research used prototype model as development system model to structure, plan and design the system. It used modelling language (UML) to make the abstraction of the program, PHP as the language program and MySQL as the database. The result of this research is the complaint will be known easier and faster as well as its evaluation and responses. Thus, the service quality of English Study Program is increased.